1973
DOI: 10.1073/pnas.70.3.653
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Transport in Normal and Rous Sarcoma Virus-Transformed Chick-Embryo Fibroblasts

Abstract: ABSTRACT3-O-methylglucose (3-OMeG) is a nonmetabolizable glucose analog and is, therefore, suitable for transport studies. 3-OMeG and glucose compete for entry into normal and Rous sarcoma virus (RSV)-transformed chick-embryo fibroblasts. Therefore, 3-OMeG can be used to study the transport of glucose in these cells. Chickembryo fibroblasts infected and transformed by RSV take up 3-OMeG at a faster rate than uninfected cells when both cell types are growing at the same rate. The rate of efflux of 3-OMeG also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…3) Both CB and phloretin were shown to trap the sugar within the cell (data not shown). The water space was calculated (14) from the plateau for 3MG uptake, assuming that at equilibrium intracellular and extracellular concentrations were similar (8,9) and is shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…3) Both CB and phloretin were shown to trap the sugar within the cell (data not shown). The water space was calculated (14) from the plateau for 3MG uptake, assuming that at equilibrium intracellular and extracellular concentrations were similar (8,9) and is shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Hatanaka et al (1970) have shown that mouse cells, when transformed with murine sarcoma virus, have an increased V max and decreased Km for 2-DG influx. Chick embryo fibroblasts transformed with Rous sarcoma virus show both an increased influx and efflux of MeG, attributable to increases in V max for this tracer (Venuta and Rubin, 1973;Weber, 1973). This increased transport of o-glucose analogues into cultured tumour cells parallels the increased level of aerobic glycolysis that has been docu mented in both animal and human tumour studies (Warburg, 1956;Sweeney et aI.…”
Section: Resultsmentioning
confidence: 99%
“…Second it was desired to study [IIC]MeG uptake by gliomas, as tissue cul ture studies have shown increased levels of MeG and 2-DG transport into isolated tumour cells (Ha tanaka et aI., 1970;Venuta and Rubin, 1973;Weber 1973). Third it was desired to study the effect of cerebral tumours on [llC]MeG transport into con tralateral cortical tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In such serum-starved sparse cultures, intracellular cAMP reaches a high level, characteristic of density-inhibited cultures (14). (20). Density-dependent inhibition of hexose uptake by uninfected cultures of chick-embryo fibroblasts and its stimulation by serum, trypsin, neuraminidase, and insulin have been reported (4,12).…”
Section: Methodsmentioning
confidence: 99%